2012
DOI: 10.3389/fncir.2012.00011
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Large-Scale Cortical Mapping Using Channelrhodopsin-2 Stimulation in Transgenic Mice Reveals Asymmetric and Reciprocal Relationships between Cortical Areas

Abstract: We have mapped intracortical activity in vivo independent of sensory input using arbitrary point channelrhodopsin-2 (ChR2) stimulation and regional voltage sensitive dye imaging in B6.Cg-Tg (Thy1-COP4/EYFP)18Gfng/J transgenic mice. Photostimulation of subsets of deep layer pyramidal neurons within forelimb, barrel, or visual primary sensory cortex led to downstream cortical maps that were dependent on synaptic transmission and were similar to peripheral sensory stimulation. ChR2-evoked maps confirmed homotopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
144
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(170 citation statements)
references
References 93 publications
(149 reference statements)
22
144
0
Order By: Relevance
“…Similarly, we repeated these experiments using antagonists of glutamatergic transmission, DNQX (500 mM) and AP5 (200 mM). Relatively high drug concentrations were required because of surface application and are consistent with blockade that we have achieved in the past 40 . Attempts to generate seed pixel correlation maps from residual spontaneous infraslow activity following treatment with TTX or DNQX and AP5 resulted in the absence of any functional structure even when presented as filled contour plots to guide visual analysis (Fig.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Similarly, we repeated these experiments using antagonists of glutamatergic transmission, DNQX (500 mM) and AP5 (200 mM). Relatively high drug concentrations were required because of surface application and are consistent with blockade that we have achieved in the past 40 . Attempts to generate seed pixel correlation maps from residual spontaneous infraslow activity following treatment with TTX or DNQX and AP5 resulted in the absence of any functional structure even when presented as filled contour plots to guide visual analysis (Fig.…”
Section: Resultssupporting
confidence: 56%
“…1b) giving us confidence that our VSD signal was reflecting truly infraslow activity. Using a giant, bilateral, cranial window experimental preparation 33,40,41 , we showed that infraslow spontaneous cortical activity exhibits bilaterally synchronous, regionally discrete areas of activation ( Fig. 2a and Supplementary Movie 1).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Optogenetic approaches have been used in rodents to probe neuronal circuits for several neurological/neurodegenerative diseases, including Parkinson disease (30) and epilepsy (31). Recent studies have also used optogenetics to map functional organization after stroke (32)(33)(34)(35). The safety and efficacy of using optogenetics in nonhuman primates has also been characterized (29,36).…”
mentioning
confidence: 99%